PERAN TRANSPORTASI BARANG KHUSUS DALAM MENDUKUNG INDUSTRI LOKAL DI KOTA KENDARI - Jumanudin; Eliyanti Agus Mokodompit (Sigma: Journal of Economic and Business, 2025)
This study aims to analyze the role of special freight transportation in supporting local industry development in Kendari City. The method used is a case study with a qualitative approach, involving 15 informants from special terminal managers, local industry players, local government, and freight transport entrepreneurs. Data were collected through semi-structured interviews, field observations, and documentation studies, then analyzed thematically. The results showed that the existence of special terminals (TERSUS), supported by adequate road infrastructure and the application of modern technology such as the Internet of Things (IoT), significantly accelerates the distribution process, reduces logistics costs, and increases the competitiveness of local products. Local government policies that support infrastructure and efficient operational cost management also contribute to the success of the special freight transportation system. The main constraints found include uneven road conditions and technological limitations on the transport fleet. This research makes an important contribution to understanding the relationship between specialized freight transportation and local industry development in medium-sized cities, and provides recommendations for the development of more sustainable transportation policies and technologies.